Christian Art and Architecture in Indonesia in the Twentieth Century: Rooted in Local Images and Buildings - Gregorius Budi Subanar (Sanata Dharma University, 2022)
In this global era, identity has become an important topic. This research presents the identity of Christian art in Indonesia as represented in visual art and the architecture of church buildings. Catholic missionaries introduced Christian visual arts through education in schools, boarding houses, and religious instructions. Thereafter, the perceptions of the Indonesian faithful were expressed through paintings and sculptures. There are three periods of the development of such expressions: (1) during the colonial era, (2) after the formations of the local artists who were sent to study abroad, and (3) the modern era. Each of these periods has its own expression.